1998
DOI: 10.1520/jfs16178j
|View full text |Cite
|
Sign up to set email alerts
|

UV-Excited Resonance Raman Spectroscopy of Narcotics and Explosives

Abstract: A 244 nm excitation Raman microspectroscope has been developed and successfully used to investigate a range of narcotics and explosives, both pure and contaminated. The instrument is quick and simple to operate and effective in identifying these compounds. The wavelength was chosen to exploit the resonance Raman effect, thereby enhancing the band intensities beyond the normal v4 enhancement associated with the shorter wavelength excitation. Another advantage over visibly excited Raman spectroscopy is the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Indications of photodegradation were substantially eliminated when the sample was placed into a small circular groove on a metal disk and then spun about the axis of the circle at 1 revolution per second. 12 This ensured that the laser was focused onto a given particle for only a very short period of time and therefore reduced the risk of photodegradation. As shown in Table 2, long acquisition times were required, in spite of the resonance Raman enhancement, as much of the powder sample being scanned was out of focus owing to variations in height of the powder on the rotating disk.…”
Section: Methodsmentioning
confidence: 99%
“…Indications of photodegradation were substantially eliminated when the sample was placed into a small circular groove on a metal disk and then spun about the axis of the circle at 1 revolution per second. 12 This ensured that the laser was focused onto a given particle for only a very short period of time and therefore reduced the risk of photodegradation. As shown in Table 2, long acquisition times were required, in spite of the resonance Raman enhancement, as much of the powder sample being scanned was out of focus owing to variations in height of the powder on the rotating disk.…”
Section: Methodsmentioning
confidence: 99%
“…Illegal drugs are generally mixed with a variety of materials that may contain contaminants, all of which may fluoresce under visible light excitation. The use of near-IR or UV excitation is required to eliminate or reduce this interference (20,21).…”
mentioning
confidence: 99%
“…Demonstration of enhancement of the Raman signal as the wavelength of the incident light approaches the wavelength of an allowed transition (resonance Raman spectroscopy) and the elimination of fluorescence when using incident radiation near 244 nm were first reported for explosives in 1997-1998 (43,44 Dieringer et al (54) have reported advances in single molecule SERS (SMSERS). Excitation of the localized surface plasmon resonance (LSPR) of a nanostructured surface or nanoparticle determines signal strength and reproducibility.…”
Section: Laser Raman Spectroscopymentioning
confidence: 99%